2014
DOI: 10.4236/ajibm.2014.41006
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Innovative Equipment in Mining: Impact on Productivity

Abstract: In this era of increased competition and rapid change, mining companies must remain attentive to all opportunities to gain an advantage over competitors. Acquisition of innovative equipment is often viewed as a way of decreasing operating costs, for example, by increasing machinery reliability. The objective of this paper is to examine the impact of new equipment on productivity in underground mining. Ten projects were examined using three indicators: the cost per meter drilled, the cost per hour of use and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This abrupt change in the mode of execution of the task was beneficial in terms of OHS. However, its impact on productivity was quite different [20]. The rules identified confirmed the difficulty of obtaining even moderate improvements as soon as one or more modifications change even part of the mode of execution of the task.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This abrupt change in the mode of execution of the task was beneficial in terms of OHS. However, its impact on productivity was quite different [20]. The rules identified confirmed the difficulty of obtaining even moderate improvements as soon as one or more modifications change even part of the mode of execution of the task.…”
Section: Discussionmentioning
confidence: 91%
“…Each project was compared to the equipment group in use over the 12-month period prior to the innovation project. Two precious studies measured the projects performance (see [20] for productivity and [21] for OHS.) Based on the results of these studies, we constructed scales for each of the performance indicators used in the present study, as shown below in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…In view of this, we suggest that future research focus on identifying the mechanisms and conditions that are involved when the introduction of innovation does help to reduce the IR. Furthermore, the success of implementation of machinery with novel technology may also be influenced by numerous human factors [14] [21] [32] [33], of which the key ones remain to be identified and measured.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature (Botha 2015a;Boudreau-Trudel et al 2014;Fisher & Schnittger 2012;Hattingh et al 2010;Horberry, Burgess-Limerick & Steiner 2010;Kaupp et al 2010;McNab et al 2013;Nong 2010;Parasuraman, Sheridan & Wickens 1997) agree with the paraphrased summary from Lynas and Horberry (2011). There have been modernisation initiatives such as proximity detection systems that have reduced vehicle-to-vehicle (and vehicle-to-person) accidents.…”
Section: State Of Knowledgementioning
confidence: 99%
“…Boudreau-Trudel et al (2014) measured the impact of new equipment and innovations in 10 mining projects based in North America. The analysis of each machinery lasted over a year, and the results showed that the introduction of new equipment did not necessarily improve productivity and efficiency.…”
Section: State Of Knowledgementioning
confidence: 99%